2022
DOI: 10.1021/jacs.2c07026
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Metal-Oxo/Peroxo Intermediates in Catalytic Water Oxidation by In Situ Electrochemical Mass Spectrometry

Abstract: Molecular catalysis of water oxidation has been intensively investigated, but its mechanism is still not yet fully understood. This study aims at capturing and identifying key short-lived intermediates directly during the water oxidation catalyzed by a cobalt-tetraamido macrocyclic ligand complex using a newly developed an in situ electrochemical mass spectrometry (EC-MS) method. Two key ligand-centered-oxidation intermediates, [(L2–)­CoIIIOH] and [(L2–)­CoIIIOOH], were directly observed for the first time, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…The above-described reaction mechanism suggests that the formation of Co IV (O) complex is not required at higher pH, and ligand oxidation reactions can drive the formation of O–O bond. However, in the TAML system, the formation of Co IV (O) species has been demonstrated and very recently identified by electrochemical mass spectrometry . Likewise, Co­(O) isoelectronic to Co V (O) mediated WO has been described in the case of [Co III -bTAML] − complex .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The above-described reaction mechanism suggests that the formation of Co IV (O) complex is not required at higher pH, and ligand oxidation reactions can drive the formation of O–O bond. However, in the TAML system, the formation of Co IV (O) species has been demonstrated and very recently identified by electrochemical mass spectrometry . Likewise, Co­(O) isoelectronic to Co V (O) mediated WO has been described in the case of [Co III -bTAML] − complex .…”
Section: Resultsmentioning
confidence: 99%
“…However, in the TAML system, the formation of Co IV (O) species has been demonstrated 32 and very recently identified by electrochemical mass spectrometry. 101 Likewise, Co(O) isoelectronic to Co V (O) mediated WO has been described in the case of [Co III -bTAML] − complex. 30 Therefore, the fine-tuning of ligand systems plays a crucial role in modulating the reaction mechanism.…”
Section: ■ Introductionmentioning
confidence: 93%
“…137 Yu et al 138 used a similar approach to extract femtoliter volumes of cytoplasm from single cells for downstream time-of-flight secondary ion mass spectrometry (ToF-SIMS) analysis, expanding the applications of nanopipettes to in situ mass spectrometry. 139 Similar techniques have been developed to deliver molecules inside single cells with high spatial resolution. 140−144 Despite these studies being linked to high-throughput downstream biological analysis, the number of collectable samples is still limited by the lack of automation.…”
Section: Conductance Microscopymentioning
confidence: 99%
“…Bury et al used an adaptation of the technique to perform subcellular biopsies from human tissue with micrometer precision . Yu et al used a similar approach to extract femtoliter volumes of cytoplasm from single cells for downstream time-of-flight secondary ion mass spectrometry (ToF-SIMS) analysis, expanding the applications of nanopipettes to in situ mass spectrometry . Similar techniques have been developed to deliver molecules inside single cells with high spatial resolution. …”
Section: High-throughput Scanning Ion Conductance Microscopymentioning
confidence: 99%
“…[16][17][18][19][20] The intermediates for water oxidation catalyzed by cobalt complexes are commonly Co(IV) species, which are nucleophilically attacked by water molecules and participate in O-O bond formation. [21][22][23] To improve the water oxidation catalytic activity of cobalt complexes, various efforts have been made to design and synthesize ligands capable of stabilizing Co(IV) intermediate species with higher reactivity. [24][25][26][27] Recent literature has revealed that some noninnocent organic ligands of cobalt complexes can participate in the water oxidation catalytic cycle via ligand oxidation.…”
Section: Introductionmentioning
confidence: 99%